The Effect of Green Bonds on Bank Stability - Supriyono, Supriyono; Athoillah, Muhammad Bareza; Febriyani, Aulia; Syanti, Liana; Wulandari, Sekar Pramesti; Nadia, Linda Putri (Jurnal Analisis Bisnis Ekonomi, 2025)
This study investigates the impact of green bond issuance on banking stability in Indonesia, emphasizing the moderating roles of capitalization and liquidity. Panel data from 47 commercial banks during the 2018–2023 period (282 bank-year observations) were analyzed using purposive sampling, with random effects, fixed effects, and OLS approaches employed. The results reveal that green bonds significantly enhance bank stability. Bank capitalization strengthens this positive effect, while liquidity weakens it. Furthermore, ROA contributes positively to stability, whereas inflation and GDP growth show no significant influence. The findings highlight that issuing green bonds alone is insufficient to improve bank stability without strong capital support. Thus, regulatory authorities should provide capital-based incentives, while bank management must strengthen capitalization and profitability to achieve sustainable financial benefits. This research contributes to financial literature by providing empirical evidence from emerging markets, particularly within the Indonesian banking system.